Application of Dairy Manure Amended with Mineral Fertilizer on Stubble-Covered Soil: Effects on Ammonia Emissions - Silva, Arejacy A. (2022)
Presented at the 1st International Electronic Conference on Agronomy, 3–17 May 2021